Recursive algorithms of adaptive lattice filters adjustment - Lekhovytskiy, D. I.; Riabukha, V. P.; Rachkov, D. S.; Semeniaka, A. V. (Technology and design in electronic equipment, 2016)
The authors analyse the algorithms intended for correction of adaptive lattice filters (ALF) parameters under K-rank (K ≥ 1) modification of estimate correlation matrix within a "sliding" over the time (range) data window. The drawbacks of methods that correct the ALF parameters based on K-fold utilization of known algorithms of rank-one (K = 1) modification are discussed. The combined algorithm (CA) of K-rank (K ≥ 1) modification is synthesized. Under considered conditions, the only one-fold utilization of the CA solves the task of ALF parameters correction. The paper demonstrates, that proposed CA reduces the computational complexity and enhances the numerical stability of procedure of ALF parameters correction as compared with the competing methods based on algorithms of rank-one modification.